Hannibal (Hannibal Lecter book 3) - Thomas Harris (New York Bantam, 2009)
You remember Hannibal Lecter: gentleman, genius, cannibal. Seven years have passed since Dr. Lecter escaped from custody. And for seven years he's been at large, free to savor the scents, the essences, of an unguarded world. But intruders have entered Dr. Lecter's world, piercing his new identity, sensing the evil that surrounds him. For the multimillionaire Hannibal left maimed, for a corrupt Italian policeman, and for FBI agent Clarice Starling, who once stood before Lecter and who has never been the same, the final hunt for Hannibal Lecter has begun. All of them, in their separate ways, want to find Dr. Lecter. And all three will get their wish. But only one will live long enough to savor the reward. . .
Keywords: Thriller; Psychological thriller